2019
DOI: 10.1161/jaha.118.011860
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Pattern Specific Protein Biomarkers for Cardiovascular Disease: A Cross‐Sectional Study in 2 Independent Cohorts

Abstract: Background Mechanisms related to the influence of diet on the development of cardiovascular disease are not entirely understood, and protein biomarkers may help to understand these pathways. Studies of biomarkers identified with multiplex proteomic methods and dietary patterns are largely lacking. Methods and Results Dietary patterns were generated through principal component analysis in 2 population‐based Swedish cohorts, the EpiHealth (EpiHealth study; n=20 817 men an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…To the best of our knowledge, only two prior studies have examined proteomic profiles of dietary patterns [38,39] Prior experimental studies indicate that gene and/or protein expression of ERBB1, PDL2, and CNTN1 is atheroprotective [40][41][42]. Further, multiple studies have reported that low concentrations of IGEBP1 are directly associated with glucose intolerance and risk of diabetes mellitus [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only two prior studies have examined proteomic profiles of dietary patterns [38,39] Prior experimental studies indicate that gene and/or protein expression of ERBB1, PDL2, and CNTN1 is atheroprotective [40][41][42]. Further, multiple studies have reported that low concentrations of IGEBP1 are directly associated with glucose intolerance and risk of diabetes mellitus [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed diet‐protein associations consistent with those reported in 3 prior studies. 32 , 33 , 34 For example, the unhealthy dietary patterns characterized in these studies were associated with higher concentrations of PAI1 (plasminogen activator inhibitor 1), MPO (myeloperoxidase), APOB (apolipoprotein B), GDF15, and HPX (hemopexin). We found that higher diet quality scores, reflecting healthier diet, were associated with lower levels of these proteins.…”
Section: Discussionmentioning
confidence: 87%
“… 1 Although the association between diet and protein biomarkers has not been well studied, we observed associations similar to those reported in previous studies. 32 , 33 The cross‐sectional Toronto Nutrigenomics and Health study demonstrated that a Western‐style dietary pattern was associated with 25 proteins involved in coagulation and lipid metabolism among 54 putative CVD biomarker proteins. 32 A Swedish study of 2 population‐based cohorts analyzed 184 CVD‐related circulating proteins and demonstrated that dietary patterns were associated with 21 proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared with national data, the full cohort well represents the Swedish population in terms of age distribution, educational level, prevalence of overweight and obesity, and smoking status ( 12 ) and the subcohort has similar distributions of these characteristics with the exception of an on average higher educational level. ( 13‐15 )…”
Section: Methodsmentioning
confidence: 99%